(3QSGdI jRjO Hf eYGhjI dhdOgs - (3jRjO Hf eYGhjI Hf CHj SajGf GdCehj,J (B64 (3g` s
(3ChdgG (B:s
(3HCf GdUMjaI dNGdO Hf jRjO Hf eYGhjI Hf CHj SajGf hjbhd ai GdfSNI GdJi cJHgG gi cJGHi HNWi ai SfI CMOi heGFI ai OGQ NGdO Hf CHj eSde Hf jRjO Hf NGdO Hf jRjO GdMeO ddg CMeOg hBef Hg hCJhcd Ydjg s
(3BNQgG (B:s
(3hHgG Je cd GdCTjGA hgj HOGjJgG hGdMeO ddg QH GdYGdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B189 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B238s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdJGQjNs